Ghosts. [Season 1] [videorecording (DVD)] - Adefope, Lolly, 1990-; Baynton, Mathew, 1980-; Baynton, Mathew, 1980-; Farnaby, Simon; Farnaby, Simon; Willbond, Ben, 1973-; Willbond, Ben, 1973-; Howick, Jim; Howick, Jim; Rickard, Laurence, 1975-; Rickard, Laurence, 1975-; Howe-Douglas, Martha, 1980-; et al. (BBC Studios, 2022)
Crumbling country mansion Button House is home to restless spirits who've died there over the centuries. Each a product of their time, they're thrown together for eternity, resigned to squabble over mundane daily gripes. But their lives or rather afterlives are thrown into turmoil when young urban couple Alison and Mike unexpectedly inherit the peaceful derelict house and plan to turn it into a bustling hotel. As the ghosts attempt to oust the newcomers, and Alison and Mike discover the true scale of the project they've taken on, fate conspires to trap both sides in an impossible houseshare.